Atomic mobility in Titanium grade 5 (Ti6Al4V) - Gierlotka W.; Lothongkum G.; Lohwongwatana B.; Puncreoburt C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Titanium grade 5 (Ti6Al4V) is a modern material that can be found in a wide spectrum of applications, from medicine to aircraft industry. The commercial alloy is a mix of a body centered cubic structure (BCC_A2) and a hexagonal closed packed structure (HCP_A3). It is obvious, that heat treatment of the alloy will change a ratio between BCC_A2 and HCP_A3 and, as a consequence, properties of a material. Information about mobility of atoms in both crystal structures allows simulations and predictions of structures’ behavior during the heat treatment and diffusion. In this work the atomic mobility in liquid, BCC_A2, and HCP_A3 phases of ternary alloy Al – Ti – V were obtained based on available literature information. Comparison between simulations and experiments shows a good agreement, hence it can be concluded that proposed set of kinetic parameters can be used for predictions and simulations of Titanium grade 5 heat treatment.